Cognitive Impairments in Spinocerebellar Ataxia Type 10 and Their Relation to Cortical Thickness. Issue 12 (30th July 2021) - Chirino‐Pérez, Amanda; Vaca‐Palomares, Israel; Torres, Diana L.; Hernandez‐Castillo, Carlos R.; Diaz, Rosalinda; Ramirez‐Garcia, Gabriel; Fernandez‐Ruiz, Juan
ABSTRACT: Background: Spinocerebellar ataxia type 10 is a neurodegenerative disorder caused by the expansion of an ATTCT pentanucleotide repeat. Its clinical features include ataxia and, in some cases, epileptic seizures. There is, however, a dearth of information about its cognitive deficits and the neural bases underpinning them. Objectives: The objectives of this study were to characterize the performance of spinocerebellar ataxia type 10 patients in 2 cognitive domains typically affected in spinocerebellar ataxias, memory and executive function, and to correlate the identified cognitive impairments with ataxia severity and cerebral/cerebellar cortical thickness, as quantified by MRI. Methods: Memory and executive function tests were administered to 17 genetically confirmed Mexican spinocerebellar ataxia type 10 patients, and their results were compared with 17 healthy matched volunteers. MRI was performed in 16 patients. Results: Patients showed deficits in visual and visuospatial short‐term memory, reduced storage capacity for verbal memory, and impaired monitoring, planning, and cognitive flexibility, which were ataxia independent. Patients with seizures (n = 9) and without seizures (n = 8) did not differ significantly in cognitive performance. There were significant correlations between short‐term visuospatial memory impairment and posterior cerebellar lobe cortical thickness (bilateral lobule VI, IX, and right X). Cognitive flexibility deficiencies correlated with cerebral cortical thickness in the left middle frontal, cingulate, opercular, and temporal gyri. Cerebellar cortical thickness in several bilateral regions was correlated with motor impairment. Conclusions: Patients with spinocerebellar ataxia type 10 show significant memory and executive dysfunction that can be correlated with deterioration in the posterior lobe of the cerebellum and prefrontal, cingulate, and middle temporal cortices. © 2021 International Parkinson and Movement Disorder Society Abstract : Patients with spinocerebellar ataxia type 10 show impairment in memory and executive function that are ataxia independent. Cognitive flexibility deficiencies correlate with thickness in specific left cerebral cortical areas, whereas short‐term visuospatial memory score correlates with bilateral posterior cerebellar lobe cortical thickness. December Infographic 2 : Cognitive Impairments in Spinocerebellar Ataxia Type 10 and Their Relation to Cortical Thickness